Analysis of the Physical Environment and Socio-Emotional Environment in an Islamic Psychopedagogical Perspective and Its Implementation in Contemporary Education - Khatimah, Rifqah Husnul; Batubara , Juliana; Deliani , Nurfarida (The Future of Education Journal, 2025)
From the standpoint of Islamic psychopedagogy and its applicability to modern education, this article explores the concepts of physical environment and socio-emotional environment.  This study examines theories from educational professionals and Quranic foundations for learning environments, which are crucial to the success of the educational process, using a qualitative library research technique. The results show that learning assessment functions not only as a measurement tool for cognitive achievement but also as a means of fostering affective and psychomotor development. Islamic principles emphasize fairness, proportionality, accountability, and appreciation for effort, which align with modern assessment approaches such as authentic assessment and competency-based evaluation. Current issues including imbalance between formative and summative assessment, the challenge of assessing character, and the integration of digital technology are also discussed. This study concludes that holistic assessment-integrating pedagogical theory and Islamic values is essential to developing an equitable and meaningful learning process.